2021
DOI: 10.1101/2021.08.16.456531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The pH Dependence of Niclosamide Solubility, Dissolution, and Morphology Motivates Potentially Universal Mucin-Penetrating Nasal and Throat Sprays for COVID19, its Contagious Variants, and Other Respiratory Viral Infections

David Needham

Abstract: Motivation: With the coronavirus pandemic still raging, prophylactic nasal and early treatment throat sprays that "puts the virus in lockdown", could help prevent infection and reduce viral load. Niclosamide has the potential to treat a broad range of viral infections if local bioavailability is optimized as mucin-penetrating solutions instead of microparticles that cannot penetrate the mucin. Experimental: pH-dependence of supernatant concentrations and dissolution rates of niclosamide were measured in buffe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…S2), and was found that only MgO could increase the pH to nearly basic, thereby improving the drug solubility. It has been reported that NIC solubility could be improved with increasing pH from 7 to 9.3 [43]. Further experiments on pH variations of samples over different time periods were studied at pH 1.2 and 6.8, clearly showing that presence of MgO could further enhance the –OH concentration under a pH of 6.8, allowing improved solubility.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…S2), and was found that only MgO could increase the pH to nearly basic, thereby improving the drug solubility. It has been reported that NIC solubility could be improved with increasing pH from 7 to 9.3 [43]. Further experiments on pH variations of samples over different time periods were studied at pH 1.2 and 6.8, clearly showing that presence of MgO could further enhance the –OH concentration under a pH of 6.8, allowing improved solubility.…”
Section: Resultsmentioning
confidence: 87%
“…that NIC solubility could be improved with increasing pH from 7 to 9.3 [43]. Further experiments on pH variations of samples over different time periods were studied at pH 1.2 and 6.8, clearly…”
Section: )mentioning
confidence: 97%
“…This is the second paper in a series of studies starting in 2021-2022 (Needham 2021(Needham , 2022) that report on the potential application of a simple aqueous buffered solution of niclosamide as a potential preventative nasal spray and early treatment throat spray for COVID-19 and other respiratory virus infections. While ostensibly simple in concept, a considerable amount of data is required to comprehensively characterize the solubility, dissolution, morphology, polymorphic states, precipitation, and interactions with common mucin-binding cellulosic polymers that would go into an effective formulation.…”
Section: Introductionmentioning
confidence: 99%